Simbiosis Pengetahuan: Menelusuri Kombinasi Penyembuhan Islami dan Tradisional dalam Naskah Mujarrabat Jawan - Alindah, Lutfiyah (Program Studi Sastra Indonesia UIN Sunan Ampel Surabaya, 2024)
There were various manuscripts spread in the archipelago. Some of the manuscripts are the source of history, literature, and religious principle, and some of them are source of medical healing as ancestral heritage. Actually, the using of traditional healing and medicines at the first is a hereditary tradition transmitted orally from one generation to the next generation. However, this traditional healing is still existed. There are some studies studied about Islam, literature, and local custom manuscripts, but studying on traditional healing and medicines manuscripts is very lack. Even though, some of the traditional healing and medicines still existed in the modern life. By using philological approach and historical approach, this research will conduct the traditional healing and medicine which are found in Mujarrabat Jawan. These approaches will cover the description of traditional healing and medicines in the manuscript and show how it practiced in everyday life. This study shows that there are some common diseases that affect people in the archipelago such as fever, toothache and sore eyes (bḗlḗk). This manuscript shows that traditional medicine is carried out in two ways. First, by using traditional ingredients such as shallots to treat burns. Second, by using Holy Qur’an readings taken from same verses in the Qur’an. This healing can be seen in the healing of toothache by reading surah al-An’am.